An appraisal of the impact of membership characteristics on the pursuit of cooperative governance : a case study of wine cooperatives in the Western Cape - Mentani, Phumlani Sphiwo (Stellenbosch : Stellenbosch University, 2011)
Thesis (MAgricAdmin )--Stellenbosch University, 2011.